Implementasi Creating Shared Value (CSV) Untuk Membangun Bisnis Berkelanjutan di Indonesia - Muh Faizal Anshori; Masiyah Kholmi (Pusat Riset dan Inovasi Nasional, 2024)
Corporate social responsibility has come to be an important a part of enterprise practices, aiming to contribute to community development and environmental maintenance.However, in practice, CSR implementation often fails to yield optimal results for companies, especially in the long term and indirect economic benefits. In response to this challenge, the concept of Creating Shared Value (CSV) emerges as an innovative paradigm shift, focusing on creating shared value for all stakeholders, including the companies themselves. State-Owned Enterprises (SOEs) and private companies in Indonesia are beginning to adopt and implement this CSV approach, demonstrating their commitment to sustainable development that provides long-term benefits for society, the environment, and economic growth. Thus, the use of the CSV concept offers opportunities for companies to enhance their contributions in creating broader positive impacts, while strengthening their position in a society and market increasingly attentive to social and environmental issues.